Hypergravity As a Tool for Cell Stimulation: Implications in Biomedicine - Genchi, Giada G.; Rocca, Antonella; Marino, Attilio; Grillone, Agostina; Mattoli, Virgilio; Ciofani, Gianni (Frontiers in Astronomy and Space Sciences, 2016)
Gravity deeply influences numerous biological events in living organisms. Variations in gravity values induce adaptive reactions that have been shown to play important roles, for instance in cell survival, growth, and spatial organization. In this paper, we summarize effects of gravity values higher than that one experienced by cells and tissues on Earth, i.e., hypergravity, with particular attention to the nervous and the musculoskeletal systems. Besides the biological consequences that hypergravity induces in the living matter, we will discuss the possibility of exploiting this augmented force in tissue engineering and regenerative medicine, and thus hypergravity significance as a new therapeutic approach both in vitro and in vivo.